2013
DOI: 10.1080/14786435.2012.731528
|View full text |Cite
|
Sign up to set email alerts
|

The mechanical response of core-shell structures for nanoporous metallic materials

Abstract: Nanoporous gold (NP-Au) exhibits microscale plasticity, but macroscopically fails in a relatively brittle manner. This current study suggests that a core-shell structure can increase both ductility and strength of NP-Au. A core Au foam structure was created using conventional dealloying methods with average ligament size of 60 nm. Nickel was then electroplated on to the NPAu with layer thicknesses ranging from 2.5 nm to 25 nm. Nanoindentation demonstrated a significant increase in the hardness of the coated Np… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 31 publications
1
8
1
Order By: Relevance
“…To check this, the hardness of nanoporous Cu was investigated before and after heating at 473 K for 2. The present softening in the Au/Cu nanocomposites is different from the previous studies on surface-modified core-shell nanoporous Au [10,11] reporting hardening by the surface coverage of the ligaments by the second phase such as Al2O3 [10] and Ni [11]. This may be related to the difference in the energy of surface deposition technique.…”
Section: Resultscontrasting
confidence: 98%
See 1 more Smart Citation
“…To check this, the hardness of nanoporous Cu was investigated before and after heating at 473 K for 2. The present softening in the Au/Cu nanocomposites is different from the previous studies on surface-modified core-shell nanoporous Au [10,11] reporting hardening by the surface coverage of the ligaments by the second phase such as Al2O3 [10] and Ni [11]. This may be related to the difference in the energy of surface deposition technique.…”
Section: Resultscontrasting
confidence: 98%
“…According to the mixing rule, when pores of a porous metal are filled with reinforcements, its mechanical characteristics such as the strength and the elastic modulus are expected to monotonically increase with increasing the volume of reinforcements. According to this mixing rule, several studies have shown that mechanical strength of nanoporous Au are enhanced by surface deposition [10,11]. However, when pores become small to nanometers, the mechanical characteristics do not necessarily obey to the mixing rule because interfaces strongly affect the mechanical characteristics.…”
mentioning
confidence: 99%
“…However, both the shell surface and the core-shell inter-face appear slightly rougher compared to the initial state. Furthermore, a limited interdiffusion is occurring at the interface, in agreement with a previous work on Au-Ni core-shell NW [33]. Note that the AuSi-NW is in a compressive state at = 0 % (σ zz ≈ -3.7 GPa), like Au-NW after the first cycle, for similar reasons.…”
Section: (D)supporting
confidence: 90%
“…Jin and Weissmuller [25] demonstrated that the strength and flow stress of the np Au can be recoverably tuned electrochemically due to OH adsorption (monolayer oxide coverage) or surface changing [25,26]. Similarly, the hardness [27][28][29], creep rate [30], elastic modulus [31], fracture behavior [32] and even plastic Poisson's ratio [33] of np Au were also found surface-sensitive. These findings testify that the surface characteristics have important impact on the mechanical response of a crystal if it's sufficiently small.…”
Section: Introductionmentioning
confidence: 99%